2018
DOI: 10.3390/ijms19103026
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation as a Biomarker of Treatment Response Variability in Serious Mental Illnesses: A Systematic Review Focused on Bipolar Disorder, Schizophrenia, and Major Depressive Disorder

Abstract: So far, genetic studies of treatment response in schizophrenia, bipolar disorder, and major depression have returned results with limited clinical utility. A gene × environment interplay has been proposed as a factor influencing not only pathophysiology but also the treatment response. Therefore, epigenetics has emerged as a major field of research to study the treatment of these three disorders. Among the epigenetic marks that can modify gene expression, DNA methylation is the best studied. We performed a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 99 publications
0
20
0
1
Order By: Relevance
“…Studies on the epigenetic impact on candidate genes of mood stabilizers, especially Li and VPA, have consistently increased in the past decade but attempts to summarize the findings have been scarce (Alladi et al, 2018;Pisanu et al, 2018). This systematic review provides a qualitative summary of the current state of knowledge of the epigenetic effects of nonantipsychotic mood stabilizers in MDD, BD, and SCZ in an attempt to define the specific mechanisms through which these agents act at the epigenomic level.…”
Section: Objectives and Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the epigenetic impact on candidate genes of mood stabilizers, especially Li and VPA, have consistently increased in the past decade but attempts to summarize the findings have been scarce (Alladi et al, 2018;Pisanu et al, 2018). This systematic review provides a qualitative summary of the current state of knowledge of the epigenetic effects of nonantipsychotic mood stabilizers in MDD, BD, and SCZ in an attempt to define the specific mechanisms through which these agents act at the epigenomic level.…”
Section: Objectives and Research Questionmentioning
confidence: 99%
“…Epimutations secondary to gene-environment interactions have been described to have a key role in the pathophysiology of major psychiatric disorders (Abdolmaleky et al, 2019) where aberrant DNA methylation and histone modification patterns have been identified. Histone acetylation levels are significantly altered in individuals with BD and, to a lesser extent, in individuals with SCZ (Gavin and Sharma, 2010;Machado-Vieira et al, 2011).There is also a reduction in global and specific DNA methylation levels in individuals with BD, MDD, and SCZ (Alladi et al, 2018). In vitro and in vivo studies have suggested the potential of mood stabilizers to reverse epimutations in major psychiatric disorders (Pisanu et al, 2018) making them a target for further research.…”
Section: Introduction Rationalementioning
confidence: 99%
“…Recent findings in the field of Psychiatry have suggested a potentially key role for epigenetic mechanisms in determining not only risk and resilience in patients and vulnerable subjects but also in modulating one's response to a given treatment. The paper by Goud Alladi and colleagues explored through a systematic review the evidence of DNA methylation mechanisms involved in the clinical treatment response in serious mental illness, specifically bipolar disorder, schizophrenia, and major depressive disorder [9]. The authors of this interesting study emphasize the potential clinical use of such markers in predicting whether a patient will respond or not to a medication, which is a highly anticipated approach in the emerging field of personalized medicine.…”
Section: Biomarkersmentioning
confidence: 99%
“…Current approaches to the discovery of novel biomarkers of diagnosis and/or therapeutic efficacy for MDD are mostly based on technological advances in neuroimaging or on the use of “Omics” technologies (i.e., genomics or other “Omics” approaches primarily used to define peripheral biomarkers of MDD) (see Gururajan et al., 2016 ; Voegeli et al., 2017 ; Busch and Menke, 2018 ). Recently, a series of systematic reviews have evaluated the effectiveness of multiple biomarkers of depression using genomics ( Menezes et al., 2019 ), epigenomics ( Goud Alladi et al., 2018 ), metabolomics ( MacDonald et al., 2018 ), antidepressant pharmacologic treatment response ( Voegeli et al., 2017 ), inflammatory biomarkers ( Smith et al., 2018 ; Yang et al., 2018 ), and neuroimaging biomarkers ( Drago et al., 2018 ; Levy et al., 2019 ; Suh et al., 2019 ).…”
Section: Clinical Interest and General Approaches For Developing Novementioning
confidence: 99%